ANALISIS SENTIMEN ULASAN PELANGGAN BATIK ECOPRINT MENGGUNAKAN NAÏVE BAYES DAN KNN CLASSIFIER - Nia Saurina (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Batik is attached to Indonesian society as a national identity and recognized as Indonesia national outfits. Batik has been used, produced and found all over Indonesia even though mostly associated to Javanese society as its main origin. Ecoprint is a technique in which plants, leaves, and leaves leave a beautiful design in terms of shape, color on a fabric medium. Sentiment analysis is the process of understanding, extracting and processing textual data automatically to get sentiment information contained in a sentence. This article is concerned on made sentiment analysis to evaluating customer satisfaction of Ecoprint Batik. We also want to know how the customer review about Ecoprint Batik and want to evaluate what Ecoprint Batik that are satisfied enough and are that customer knows that Ecoprint Batik are environmentally friendly, using Naïve Bayes and KNN classifier. In accordance with the tweet data of 5,736 positive sentiments and 1,707 negative sentiments, we can see that ecoprint batik buyers are satisfied with ecoprint batik products. In addition, looking at the data train as 17,197 tweets, there are 39 tweets that know that ecoprint batik is environmentally friendly, for the rest consumers of batik ecoprint write more about the quality of ecoprint batik.